PENGARUH PEMBERIAN INFORMASI TERHADAP PENGETAHUAN DAN SIKAP WANITA USIA SUBUR ( WUS ) TENTANG IMUNISASI HPV DI WILAYAH KERJA PUSKESMAS SEI LANGKAI KOTA BATAM TAHUN 2018 - Dewi, Twingga Hariati; Nurul Aulia, Devy Lestari (Universitas Batam, 2018)
Human Papilloma Virus vaccination is one of the premier prevention efforts for protecting women of the cervical cancer. Approximately, 70% of the cervical cancer is caused by the 16 and 18 virus of HPV. The cervical cancer is the most problem that happened in Indonesia lately, and 70% of them are found in advanced stadium. The aim of this research is for knowing or recognizing the influence of giving information about HPV immunization to the women child- bearing ageâ€™s knowledge and attitude. This research applies pretest â€“ posttest one group design and takes ninety-nine participants of women of child â€“ bearing age as the samples. The samples are taken by using â€œpurposive samplingâ€. And have done in February to August 2018 in SeiLangkai Puskesmas, Batam city.Â The data has analyzed by using â€œT- Test analysisâ€. The result of this research indicates the average of the knowledge of women child- bearing age is increase. That is proven by the data of the research, in which, before the information is given the average of their knowledge is 7, 91 Â± SD 1, 67; and its increase to 10, 60 Â± SD 1, 64 from the total score 15 and increase to 2, 69 after the information is given to them. And the average of their attitude before the giving information is 32, 95 Â± SD 4, 02, and it is increase to 38, 04 Â± SD 4, 24 from the total score 60 and increase to 5, 09.Â The result of â€œT- Test â€œexperiment is p-0,000 (p< 0, 05).Â The conclusion of this research is there is an influence of giving information about HPV Immunization to the women child â€“ bearing ageâ€™s knowledge and attitude. My suggestion is Respondents are able to increase or improve their knowledge and attitude about the benefits of HPV Immunization, and I wish they would desire to do the HPV Immunization.